Potentialities of pedagogical documentation as an intertwined research process with children and teachers in slow pedagogies. Issue 2 (4th March 2022) - Carlsen, Kari; Clark, Alison
ABSTRACT: This article seeks to look below the surface of pedagogical documentation with a temporal lens. We focus on the potentialities of pedagogical documentation as an intertwined research process with children and teachers as learners in 'slow pedagogies' (Clark [2020]. "Towards a Listening ECEC System: Valuing Slow Pedagogy and Slow Knowledge." In Transforming Early Childhood in England, edited by P. Moss and C. Cameron. London: UCL Press). The article brings together two research studies: a small-scale study of Norwegian early childhood practice that adds an in-depth and a cross-national study based on key-informant interviews that adds breadth to thinking about the value of pedagogical documentation. We present a visual proposal, which extends our understanding of the ongoing process of children's explorations and teacher's observations, reflections and didactic decisions in open-ended learning processes (Carlsen [2021]. Reggio Emilia – Atelierkultur og Utforskende Pedagogikk [Reggio Emilia – Atelier Culture and Exploratory Pedagogy]. Bergen: Fagbokforlaget). The visualization shows the reciprocity in the co-researching process with children and teachers and contributes to the understanding of the temporal dimension and the complexity of the process of pedagogical documentation. The discussion points to the importance of early childhood teachers being able to 'catch the moments' in young children's explorations and the value of 'stretched time' that can be supported and recorded through the process of pedagogical documentation.